THE IMPORTANCE AND BENEFITS OF LEARNING FOREIGN LANGUAGES (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2025)
The article emphasizes the essential role of foreign language learning in today's globalized world. It outlines various advantages, including personal development through improved cognitive skills and self-esteem, enhanced educational opportunities that facilitate access to global knowledge, and career benefits in an increasingly competitive job market. Furthermore, it highlights how language proficiency fosters cultural awareness, enriches travel experiences, and enhances engagement with digital content. Ultimately, the article advocates for multilingualism as a crucial asset for individuals and societies, encouraging young learners to embrace language education for a more connected future.